2002
DOI: 10.1007/s00425-002-0842-1
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring flux through the oxidative pentose phosphate pathway using [1- 14 C]gluconate

Abstract: The aim of this work was to examine the metabolism of exogenous gluconate by a 4-day-old cell suspension culture of Arabidopsis thaliana (L.) Heynh. Release of (14)CO(2) from [1-(14)C]gluconate was dependent on the concentration in the medium and could be resolved into a substrate-saturable component (apparent K(m) of approximately 0.4 mM) and an unsaturable component. At an external concentration of 0.3 mM, the rate of decarboxylation of applied gluconate was 0.2% of the rate of oxygen consumption by the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…To probe the activity of the OPPP, leaf discs were incubated with either [U- 14 C]Glc or [1-14 C] gluconate (Table II). Release of 14 CO 2 from the latter occurs specifically during the decarboxylation of 6-phosphogluconate to ribulose 5-phosphate catalyzed by 6-phosphogluconate dehydrogenase and thus provides a direct measure of flux through the oxidative steps of the pentose phosphate pathway (Garlick et al, 2002). The uptake and metabolism of both substrates was significantly greater in the dark than in the light, and the release of extractable G6PDH activity from leaves sampled in the light or dark: control (black bars), AS2/1 (white bars), and AS6 (gray bars).…”
Section: Impact Of Reduced Cp12 Content On the Oppp And The Malate Valvementioning
confidence: 99%
“…To probe the activity of the OPPP, leaf discs were incubated with either [U- 14 C]Glc or [1-14 C] gluconate (Table II). Release of 14 CO 2 from the latter occurs specifically during the decarboxylation of 6-phosphogluconate to ribulose 5-phosphate catalyzed by 6-phosphogluconate dehydrogenase and thus provides a direct measure of flux through the oxidative steps of the pentose phosphate pathway (Garlick et al, 2002). The uptake and metabolism of both substrates was significantly greater in the dark than in the light, and the release of extractable G6PDH activity from leaves sampled in the light or dark: control (black bars), AS2/1 (white bars), and AS6 (gray bars).…”
Section: Impact Of Reduced Cp12 Content On the Oppp And The Malate Valvementioning
confidence: 99%
“…This is a well-established response (Averill et al, 1998;Garlick et al, 2002) in which an increased demand for NADPH for nitrite assimilation leads to an increased flux through the OPP pathway via the response of glucose 6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase to the NADPH/NADP ratio. Titration of KNO 2 concentration against OPP pathway flux in an Arabidopsis cell suspension culture revealed that 5 mM nitrite is sufficient to lead to a significant increase in flux within 3 h ( Figure 3A).…”
Section: The Degree Of Association Of Glycolytic Enzymes With Potato mentioning
confidence: 99%
“…Flux through the OPP pathway was estimated based on the method of Garlick et al (2002) in which the labeling of CO 2 when cells are incubated with either [1-14 C]gluconate or [6-14 C]glucose is monitored.…”
Section: Measurement Of Opp Pathway Fluxmentioning
confidence: 99%
“…6-AN impairs OPPP because it is a potent inhibitor of the phosphogluconate dehydrogenase (Kohler et al, 1970;Garlick et al, 2002), whereas trehalose supply results in an increased accumulation of T6P due to its inhibitory action on T6P phosphatase activity (Schluepmann et al, 2004).…”
Section: Regulation Of Root Ion Transporters Bymentioning
confidence: 99%